2021
DOI: 10.1002/nano.202100193
|View full text |Cite
|
Sign up to set email alerts
|

Rose petal effect: A subtle combination of nano‐scale roughness and chemical variability

Abstract: Rose petals may involve high water contact angles together with drop adhesion which are antagonistic wetting properties. Petal surfaces have a cuticle which is generally considered a continuous, hydrophobic lipid coating. The peculiar properties of rose petals are not fully understood and have been associated with high surface roughness at different scales. Here, the chemical and structural features of natural upper and lower petal surfaces are analyzed by atomic force microscopy (AFM). Both rose petal surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 60 publications
2
20
0
Order By: Relevance
“…Unlike the sporophyte, no cuticle was observed on the gametophyte by LM proceedings (Figure 1D), but a very thin osmiophilic layer external to the gametophyte epidermis was observed by TEM (Figure 1H). As well in the present study, Cook & Graham (1998) (Almonte et al, 2021), have demonstrated the presence of cell wall constituents among the cuticle layers, contradicting the traditional idea that the cuticle is free of polysaccharides and "continuous" (Brongniart, 1830;Jeffree et al, 2006). This cuticle chemical heterogeneity suggests a variation of the hydrophobic property in different regions of the same plant surface, facilitating the bidirectional permeability of water and solutes, the wettability of plant surfaces, altering mechanical resistance and, therefore, changing the interaction with microorganisms and contaminants deposited on these surfaces (Guzmań-Delgado et al, 2014;Almonte et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Unlike the sporophyte, no cuticle was observed on the gametophyte by LM proceedings (Figure 1D), but a very thin osmiophilic layer external to the gametophyte epidermis was observed by TEM (Figure 1H). As well in the present study, Cook & Graham (1998) (Almonte et al, 2021), have demonstrated the presence of cell wall constituents among the cuticle layers, contradicting the traditional idea that the cuticle is free of polysaccharides and "continuous" (Brongniart, 1830;Jeffree et al, 2006). This cuticle chemical heterogeneity suggests a variation of the hydrophobic property in different regions of the same plant surface, facilitating the bidirectional permeability of water and solutes, the wettability of plant surfaces, altering mechanical resistance and, therefore, changing the interaction with microorganisms and contaminants deposited on these surfaces (Guzmań-Delgado et al, 2014;Almonte et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…As well in the present study, Cook & Graham (1998) (Almonte et al, 2021), have demonstrated the presence of cell wall constituents among the cuticle layers, contradicting the traditional idea that the cuticle is free of polysaccharides and "continuous" (Brongniart, 1830;Jeffree et al, 2006). This cuticle chemical heterogeneity suggests a variation of the hydrophobic property in different regions of the same plant surface, facilitating the bidirectional permeability of water and solutes, the wettability of plant surfaces, altering mechanical resistance and, therefore, changing the interaction with microorganisms and contaminants deposited on these surfaces (Guzmań-Delgado et al, 2014;Almonte et al, 2021). The simpler cuticle detected by TEM analysis in the P. laevis gametophyte (Figures 1F, H) may be related to a lower lipidization, perhaps due to a lower wax content (Figure 3A), observed in the present study, and a greater presence of wall polysaccharides associated with the cuticular layer.…”
Section: Discussionsupporting
confidence: 91%
“…This same rationale also applies for the negative replicas, which have the same degree of homogenization as that of the positive replicas themselves and thus explains the higher h c for YRN than on RRN. So, in previous studies, the influence of the complex hierarchical structures that are omnipresent on these biological surfaces over the static wetting states have been studied, 13,14,32 but the dynamic wetting states over such short times have been missing. This is shown here for the first time that over a much shorter time such as during droplet impact, the same hierarchical structures that show sticky superhydrophobicity reveal a myriad of other wetting states including the completely opposite superhydrophobicity as well.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The “lotus effect” is a hallmark of such structural superhydrophobicity, which has been exploited exhaustively by the research community for its adaptation in the fabrication of self-cleaning and low-maintenance surfaces. On the other hand, sticky hydrophobicity of the rose petals has recently gained much attention from researchers as they exhibit contrasting properties of high equilibrium contact angle (i.e., low foothold) along with their strong adhesive nature. The origin of such sticky hydrophobicity of the petals is believed to be the Cassie-impregnated wetting state, where the liquid gets into the microbumps present on the surface of the petal but is unable to impregnate the nanowrinkles interspersed on the microbumps. , Owing to this unique hierarchical patterns, the liquid drop remains totally stuck on the surface, even when the conformation of the drop is changed from the sessile to the pendant. A more recent study revealed that this petal effect may also find its origin in the chemical heterogeneity at the nanoscale . Another molecular dynamics simulation study showed that the higher wettability of the nanowrinkles is the reason for such high adhesion .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation